2005
DOI: 10.1097/01.mpa.0000181486.42646.4e
|View full text |Cite
|
Sign up to set email alerts
|

Pancreaticoduodenectomy in Adults With Congenital Intestinal Rotation Disorders

Abstract: Congenital intestinal malrotation is a developmental anomaly resulting from interruption of the physiological herniation and return to the abdominal cavity of the midgut during the 6th to 10th week of embryological development. Normal vascular and anatomic relationships used as landmarks during pancreaticoduodenectomy (PD) are altered in patients with congenital malrotation. We present 3 cases of PD in adults with congenital intestinal rotation disorders. Three adult patients with congenital rotational disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…[ 11 ] Additionally, the hepatic artery originating from the SMA has been reported in multiple cases. [ 4 , 12 , 13 ] Suprarenal IVC interruption with azygos continuation, as observed in our patient, is also a common abnormality. [ 14 ] The presence of a preduodenal portal vein is associated with polysplenia.…”
Section: Discussionsupporting
confidence: 55%
“…[ 11 ] Additionally, the hepatic artery originating from the SMA has been reported in multiple cases. [ 4 , 12 , 13 ] Suprarenal IVC interruption with azygos continuation, as observed in our patient, is also a common abnormality. [ 14 ] The presence of a preduodenal portal vein is associated with polysplenia.…”
Section: Discussionsupporting
confidence: 55%
“…11,20 Mateo et al reported one case of intestinal malrotation with an ampullary villous adenoma. 21 It is not single in this case. Gardner-Thorpe et al also reported a case of 66-year-old woman with congenital rotational abnormalities accompanied with a 9-cm ampullary villous adenoma.…”
Section: Discussionmentioning
confidence: 92%
“…Although there is no direct evidence for the relationship between a congenital abnormality and carcinogenesis, several studies may provide valuable clues to support the speculation that intestinal malrotation in adults is a possible underlying cause of pancreatitis and pancreatic tumors listed in Table 3. [21][22][23] Midgut volvulus in adults usually results in vascular compromise, and chronic intestinal ischemia and infl ammation. 14 Chronic infl ammation is one of factors associated with the formation of several malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal malrotation occurs during the sixth to tenth weeks of embryological development. It affects the position and peritoneal attachments of the bowel with alteration in vascular and anatomic relationships [1,2], and it has three stages: nonrotation (absent), incomplete rotation, and malfixation [2,3]. Cholangiocarcinoma (CCA) is a heterogeneous group of tumors derived from cells of the biliary tree that represent the second most frequent primary liver tumor [4].…”
Section: Introductionmentioning
confidence: 99%